DANCR deletion retards the initiation and progression of hepatocellular carcinoma based on gene knockout and patient-derived xenograft in situ hepatoma mice model. (1st December 2022) - Gan, Xiaojie; Ding, Dongyang; Wang, Mengchao; Yang, Yuan; Sun, Dapeng; Li, Wen; Ding, Wenbin; Yang, Fu; Zhou, Weiping; Yuan, Shengxian
Abstract: Our previous study has demonstrated that the expression level of long noncoding RNA (lncRNA)-differentiation antagonizing non-protein coding RNA ( DANCR ) increases in hepatocellular carcinoma (HCC), contributing to the initiation and aggravation of such kind of malignant tumor, which is recognized as a promising therapeutic target for patients with HCC. To further investigate the effect of DANCR on HCC in preclinical models, we generated a Dancr knockout (KO) mice model by Cas9/gRNA technology and a patient-derived xenograft (PDX) in situ hepatoma mice model using immunodeficient mice and utilized adeno-associated virus 8 (AAV8) delivery DANCR- shRNA system to silence the expression of DANCR in xenograft tumor . Here, we reported that Dancr expression mainly occurred in hepatocytes and its depletion significantly alleviated hepatic fibrosis in mice and showed a prospective result with smaller tumor size and fewer number of tumors in HCC preclinical mice model. Additionally, we found that the expression of Dancr in mice cirrhotic liver was positively correlated with the content of Dancr in serum. Overall, DANCR KO can inhibit the occurrence and development of HCC and is a target worthy of further study in patients with HCC. Highlights: Dancr KO significantly alleviates hepatic fibrosis in mice. Dancr KO reduces the hepatocarcinogenesis in mice. DANCR interference retards the progression of the HCC in PDX orthotopic mice model.